A CO 2 Catalytic conversion catalyst and its preparation method and application
By using silicon-aluminum composite oxide support and catalysts with components such as CuO, MnO2, Fe2O3, etc., the problems of poor stability of CO2 reverse water gas conversion catalyst at high temperatures and insufficient activity at low temperatures are solved, and high CO2 conversion rate and CO selectivity are achieved, which is suitable for industrial application of methanol indirect method for CO2.
Patent Information
- Application Number
- CN202411822693.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing CO2 counterwater gas conversion catalysts have poor stability at high temperatures and insufficient CO conversion and CO selectivity at low temperatures, which limits the industrial application of methanol indirect method for CO2.
Silicon-aluminum composite oxide is used as the support, CuO is supported as the first active component, MnO2 and Fe2O3 are used as the second active component, and CeO2, ZrO2, and ZnO are used as additives. The activity, selectivity and stability of the catalyst are improved through specific preparation methods and process conditions.
Under the conditions of 0.1~2.0MPa, H2/CO2=1~4, the catalyst's CO2 conversion rate reached 23% at 300 ℃, and the CO selectivity was close to 100%. It reacted continuously at 550 ℃ for 500 h without inactivation, and had good low-temperature activity and high-temperature stability.
Smart Images

Figure CN119281315B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of CO2 reverse water-gas shift reaction, and relates to a CO2 catalytic conversion catalyst and a preparation method and application thereof. Background Art
[0002] In order to better achieve carbon peak and carbon neutrality, the key lies in the resource utilization of CO2. At present, the main ways of CO2 conversion and utilization include: CO2 methanation, CO2 to methanol, and CO2 reverse water gas shift (RWGS). Among them, methanol, as an important chemical raw material, is widely used in the synthesis reactions of many fine chemicals such as olefins. In addition, methanol itself is also a green fuel that can be mixed with gasoline. It has the advantages of high combustion energy release, easy storage, and does not contain environmental pollution components such as sulfur and nitrogen. Therefore, CO2 to methanol has become one of the most promising ways of CO2 conversion and utilization for industrial applications.
[0003] There are two main ways to produce methanol from CO2: direct CO2 production and indirect CO2 production. The direct CO2 production of methanol is limited by thermodynamic equilibrium and is limited to 200-300 o C, under high pressure (5-10MPa), the equilibrium conversion rate of CO2 is 20%~30%, and the equilibrium yield of methanol is less than 21%; the indirect method of producing methanol from CO2 is to convert CO2 into CO through the reverse water gas shift reaction, and then synthesize methanol from CO, CO2 and H2. This method can break through the thermodynamic equilibrium limit, and the equilibrium conversion rate of CO2 is ≥45%, and the equilibrium yield of methanol is ≥40%. Therefore, the indirect method of producing methanol from CO2 is more conducive to improving the utilization efficiency of CO2 and the yield of methanol, and the economic benefits are more significant.
[0004] The key to the indirect production of methanol from CO2 is the CO2 reverse water gas shift process. This reaction is an endothermic process, and high temperature is conducive to the high selectivity of CO2 to CO. However, high temperature conditions easily lead to deactivation behaviors such as catalyst agglomeration, sintering of active components, and carbon deposition, resulting in reduced catalytic efficiency. At the same time, due to the endothermic nature of the reaction, it is difficult to obtain a high CO2 conversion rate under mild conditions, and CO2 methanation reactions are prone to occur at low temperatures, resulting in reduced CO selectivity. Therefore, the development of high-temperature stable and low-temperature efficient CO2 reverse water gas shift catalysts is the key to promoting the large-scale industrial application of indirect production of methanol from CO2.
[0005] Chinese patent application CN106881082A discloses a 0.1% Ir / TiO2 catalyst that can be used at H2 / CO2=1, 600 °C, and 50000 mL / h·g catUnder the conditions of H2 / CO2=1, 500℃, 3000h, CO2 conversion rate is 30%, CO selectivity is 96%. CN 108144637 B discloses a 0.5%Pt-KOH / KLTL catalyst. -1 Under the conditions of , CO2 conversion rate is 27% and CO selectivity is 100%. Another Chinese patent application CN111250121A discloses a 1% Pd / MoC catalyst, which can be used at H2 / CO2=4, 400℃, 4560 mL / h·g cat Under the conditions of H2 / CO2=3, 500℃, 60000 mL / h·g cat Under the conditions of , CO2 conversion was 17.8% and CO selectivity was 100%.
[0006] The above patents all use precious metals as active components, but the CO2 conversion rate needs to be improved, and precious metal catalysts are expensive, which limits their large-scale industrial application.
[0007] At present, the non-precious metal catalysts used in the research of CO2 reverse water gas shift reaction are mainly copper-based catalysts. For example, Chinese patent application CN107497439A discloses a 10% Cu-CeO2 catalyst, which can be used to generate a 10% Cu-CeO2 catalyst at H2 / CO2=1, 600℃, and 6000 mL / h·g cat Under the conditions of , the CO2 conversion rate is 31.79%. The CO2 conversion rate on the catalyst needs to be improved, and there is no data on CO selectivity. After 450 min of continuous reaction, the CO2 conversion rate on the catalyst decreased by 12%, and the stability is poor. CN 103230799A discloses a CuZnK catalyst, H2 / CO2=3, 400 °C, 5000 h -1 Under the conditions, the CO2 conversion rate is 30.3% and the CO selectivity is 89.2%. By-products such as alcohols, CH4, and oxygen-containing compounds are also produced. The accumulation of by-products eventually leads to a decrease in catalyst performance and deactivation. Therefore, the CO selectivity and catalyst stability on this catalyst need to be improved.
[0008] At present, copper-based catalysts have been widely studied in the CO2 reverse water-gas shift reaction due to their low price, good low-temperature activity, and high CO selectivity. However, since this reaction is an endothermic reaction, high temperature is conducive to improving catalytic activity. However, under high temperature and strong reducing atmosphere, copper-based catalysts are prone to sintering and agglomeration, resulting in poor high-temperature stability. Therefore, the development of copper-based CO2 reverse shift catalysts with high activity, high selectivity and / or high stability is the key to realizing the industrial application of CO2 indirect methanol production. Summary of the invention
[0009] The purpose of the present invention is to provide a CO2 catalytic conversion catalyst and its preparation method and application, so as to further improve its activity, selectivity and stability in the CO2 reverse water gas shift reaction.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] In a first aspect, the present invention provides a method for preparing a CO2 catalytic conversion catalyst, comprising the following steps:
[0012] (1) Weigh a silicon source and an aluminum source to prepare a silicon-aluminum aqueous solution, mix it with an inorganic acid aqueous solution, and stir to form a white sol until the viscosity reaches 1200-2000 mPa·S;
[0013] (2) centrifuging, washing and drying the sol obtained in step (1) to obtain white silicon-aluminum composite oxide powder, adding a binder and rolling into balls to obtain a silicon-aluminum composite oxide carrier precursor;
[0014] (3) Weighing a first active component precursor, a second active component precursor and an auxiliary component precursor, dissolving and stirring them with water as a solvent to obtain a mixed solution;
[0015] (4) The silicon-aluminum composite oxide support precursor in step (3) is immersed in the mixed solution, dried, and calcined to obtain a CO2 catalytic conversion catalyst.
[0016] Furthermore, the prepared CO2 catalytic conversion catalyst includes a silicon-aluminum composite oxide carrier, and a first active component, a second active component and an auxiliary component loaded on the silicon-aluminum composite oxide carrier, wherein the first active component is CuO, the second active component is an oxide of Mn and / or Fe, and the auxiliary component is an oxide of at least one of Ce, Zr or Zn.
[0017] Furthermore, in the silicon-aluminum composite oxide carrier, the mass content of SiO2 is 50% to 96%, and illustratively, it can be 50%, 60%, 70%, 80%, 90%, 96%, etc., or it can be any other value within the above range, and the mass content of Al2O3 is 4% to 50%, and illustratively, it can be 4%, 10%, 20%, 30%, 40%, 50%, etc., or it can be any other value within the above range.
[0018] The binder in the present invention is to improve the balling rate and strength of the carrier in the ball rolling forming, and its dosage can be adjusted as needed. Binders are divided into two categories: organic and inorganic. Organic binders are decomposed and removed during the subsequent roasting process, and inorganic binders cannot be completely removed during the roasting process, such as silica sol and aluminum sol, which eventually exist in the form of silicon oxide and aluminum oxide. Since the amount of binder added is very low, the effect on the overall silicon oxide and aluminum oxide content is very small and can be ignored. Exemplarily, the mass ratio of silicon aluminum composite oxide powder to binder is (1:0.005~0.05), and the binder is one or more of silica sol, aluminum sol, bentonite, sodium methyl cellulose, starch, attapulgite, and kaolin.
[0019] Further, the first active component is 1-15% of the mass of the silica-aluminum composite oxide support, and illustratively, it can be 1%, 5%, 7.5%, 10%, 15%, etc., or any other value within the above range; the second active component is 0.5-7.5% of the mass of the silica-aluminum composite oxide support, and illustratively, it can be 1%, 2.5%, 5%, 7.5%, etc., or any other value within the above range; the auxiliary agent component is 0.5-7.5% of the mass of the silica-aluminum composite oxide support, and illustratively, it can be 1%, 2.5%, 5%, 7.5%, etc., or any other value within the above range.
[0020] Furthermore, in step (1), the silicon source is selected from one or more of silica sol, sodium silicate, and silicon oxide powder.
[0021] Furthermore, in step (1), the aluminum source is selected from one or more of aluminum sol, pseudo-boehmite, quick-de-powdering, and alumina powder.
[0022] Furthermore, in step (1), the inorganic acid is one or more of nitric acid, hydrochloric acid or sulfuric acid.
[0023] Furthermore, in step (1), the H + The molar ratio of the total amount of SiO2+Al2O3 in the silicon source and the aluminum source is 0.5~2:1.
[0024] Furthermore, in step (2), washing is performed once or repeatedly for multiple times until the conductivity of the filtrate is lower than 200 μs / cm.
[0025] Furthermore, in step (2), the drying temperature is 100-120°C.
[0026] Furthermore, in step (2), the mass ratio of the white silicon-aluminum composite oxide powder to the binder is (1:0.005-0.05), and the binder is one or more of silica sol, aluminum sol, bentonite, sodium methyl cellulose, starch, attapulgite, and kaolin.
[0027] Furthermore, in step (3), the first active component precursor is copper nitrate.
[0028] Furthermore, in step (3), the second active component precursor is a nitrate of Mn and / or Fe.
[0029] Furthermore, in step (3), the auxiliary agent component precursor is a nitrate of Ce and / or Zr.
[0030] Furthermore, in step (4), the impregnation process is specifically as follows: ultrasonic impregnation for 0.5 to 2 h to achieve the desired loading amount.
[0031] Furthermore, in step (4), the drying process is specifically: drying at 100-120°C for 6-12 hours.
[0032] Furthermore, in step (4), the calcination process is specifically as follows: calcination at 350-600°C for 2-6 h.
[0033] The present invention uses silicon-aluminum composite oxide as a carrier, CuO as a first active component, MnO2, Fe2O3, etc. as a second active component, CeO2, ZrO2, ZnO, etc. as an auxiliary agent, and the large specific surface area of the carrier improves the dispersion of the active component, reduces the grain size, and helps to stabilize the catalyst; in the preparation process, the sol formed between the silicon source and the aluminum source gradually forms a cross-linking effect under stirring conditions, forming a stable Si-O-Al tetrahedral structure that is not possessed by conventional physical mixing, so that the carrier has high thermal stability and better water resistance, which helps to improve the stability of the catalyst under high temperature and high humidity conditions, and the SiO2 and Al2O3 in the carrier are mutually adjusted, so that it has a moderate alkalinity strength and a large number of alkaline sites, which helps to promote the formation of moderate strength adsorption between CO2 and the silicon-aluminum composite oxide carrier, thereby promoting CO2 adsorption and catalytic conversion, and improving CO2 conversion rate. The addition of the second active component allows the metals to form a synergistic effect, changes the valence distribution of Cu through the electronic effect, significantly improves the dispersion of CuO, further reduces the CuO grain size, and improves the catalyst activity. The addition of the additive significantly reduces the reduction temperature of the catalyst and improves the reduction performance of the catalyst. At the same time, the addition of the additive increases the amount of highly dispersed CuO on the surface, improves the low-temperature activity of the catalyst, forms a solid solution structure between the additive and CuO, further improves the dispersion of CuO, reduces the CuO grain size, effectively stabilizes the active components, and improves the stability of the catalyst.
[0034] The present invention can achieve the following conditions: 0.1~2.0MPa, H2 / CO2=1~4, air velocity 3000~24000h -1 Under the conditions of low temperature of 300 °C, CO2 conversion rate (23%) is close to the thermodynamic equilibrium value, CO selectivity is close to 100%, and at atmospheric pressure, 550 °C, H2 / CO2=3, and space velocity of 24000h -1 Under the conditions of continuous reaction for 500 h, the CO2 conversion rate (54.73%) was close to the thermodynamic equilibrium value, the CO selectivity was close to 100%, there was no deactivation phenomenon, and it had good low-temperature activity and high-temperature stability.
[0035] In a second aspect, the present invention provides a CO2 catalytic conversion catalyst, which is prepared using the preparation method described above.
[0036] Furthermore, the specific surface area of the silicon-aluminum composite oxide support is 500-800 m 2 / g, pore volume is 0.4~0.8cm 3 / g, particle strength ≥60 N / particle, particle strength decreases by <10% after 550 ℃ water vapor treatment, and particle breakage rate in liquid water is <1%.
[0037] Furthermore, the specific surface area of the catalyst is 350~650 m 2 / g, pore volume is 0.3~0.7 cm 3 / g, CuO grain size is less than 2nm.
[0038] In a third aspect, the present invention provides an application of a CO2 catalytic conversion catalyst in a CO2 reverse water gas shift reaction. Specifically, the catalyst of the present invention (0.1-2.0 MPa, H2 / CO2=1-4, space velocity 3000-24000 h -1 ) When the temperature is as low as 300 ℃, the CO2 conversion rate reaches 23%, and the CO selectivity is close to 100%. At normal pressure, 550 ℃, H2 / CO2=3, and a space velocity of 24000h -1 Under the conditions of , the CO2 conversion rate reached 54.73%, the CO selectivity was close to 100%, and the reaction was continued at 550 ℃ for 500 h without deactivation.
[0039] Compared with the prior art, the present invention has the following advantages:
[0040] (1) Compared with the commonly used alumina carrier in industry, the silicon-aluminum composite oxide carrier of the present invention has a larger specific surface area, which helps to improve the dispersion of active components, reduce the grain size of active components, inhibit the aggregation and growth of active components, and improve the stability of the catalyst; compared with the molecular sieve carrier, the relatively large pore size helps the reactants to diffuse in the pores, promotes the increase of reaction rate, and effectively inhibits the accumulation of intermediate products and by-products, thereby improving the stability of the catalyst; in addition, the silicon-aluminum composite oxide carrier has good high thermal stability and excellent water resistance, which helps to improve the stability of the catalyst under high temperature and high humidity conditions. The SiO2-Al2O3 in the silicon-aluminum composite oxide carrier adjusts each other, so that it has a moderate alkaline strength and a large number of alkaline sites, which form a moderate adsorption effect with CO2, thereby improving the adsorption and catalytic conversion capacity of CO2.
[0041] (2) The CO2 catalytic conversion catalyst of the present invention uses CuO as the first active component, and has good CO2 reaction activity and CO selectivity; the introduction of the second active component forms a synergistic effect with the first active component, and the electronic effect between the two changes the valence distribution of Cu, which helps to improve the dispersion of CuO, reduce the grain size, effectively inhibit the aggregation and growth of the active component, and improve the activity and stability of the catalyst; the introduction of the auxiliary agent improves the reduction performance of the catalyst, reduces the reduction temperature, increases the amount of highly dispersed CuO on the surface, and increases the low-temperature activity; on the other hand, the auxiliary agent forms a solid solution structure with CuO, further improves the dispersion of CuO, reduces the CuO grain size, stabilizes the active component, and improves the stability of the catalyst. In addition, the addition of the second active component and the auxiliary agent promotes the efficient conversion of the reaction intermediate product into the target product CO, effectively inhibits the CO2 methanation side reaction, prevents the intermediate product and the by-product from occupying the catalyst surface and blocking the catalyst pores, thereby greatly improving the stability and service life of the catalyst.
[0042] (3) The CO2 catalytic conversion catalyst of the present invention uses silicon-aluminum composite oxide as a carrier, which is resistant to liquid free water and high-temperature water vapor. In the presence of free water and high-temperature water vapor, the particle strength can maintain more than 90% of the fresh sample, avoiding pulverization and breakage in industrial applications, and improving the stability of industrial equipment operation. At the same time, the catalyst preparation process is simple, the production cost is low, and it has significant cost advantages, which is conducive to industrial production and application and has potential industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The CO2-TPD spectra of the carriers in the embodiments and comparative examples;
[0044] Figure 2 It is the XRD spectra of the catalysts in the embodiments and comparative examples;
[0045] Figure 3 It is the H2-TPR spectrum of the catalyst in the embodiment and the comparative example;
[0046] Figure 4 In-situ infrared spectra of the catalysts in the examples and comparative examples;
[0047] Figure 5 It is the stability performance of the catalyst in Example 1. DETAILED DESCRIPTION
[0048] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0049] In the following embodiments, each test method is specifically as follows:
[0050] The nitrogen adsorption and desorption experiment (BET) was tested on an ASAP 2020 surface area and pore size analyzer. The specific test method was as follows: a certain amount of catalyst sample was weighed, and a N2 adsorption and desorption test was performed after pretreatment at 300 °C. The BET method was used to calculate the specific surface area of the sample, and the BJH model was used to calculate the pore volume and average pore size.
[0051] The strength test was carried out on a particle strength tester (DL3-500). The specific test method was as follows: 30 silicon-aluminum composite oxide carriers were taken, and a single sample was placed on the test platform of the particle strength tester. The compressive strength was tested particle by particle, and then the average strength of the silicon-aluminum composite oxide carrier was calculated.
[0052] The test method for the breakage rate in liquid water is as follows: take 500 g of silicon-aluminum composite oxide support, soak it in 500 mL of water for 30 min, observe the particle breakage, and calculate the breakage rate.
[0053] X-ray diffraction (XRD) was used to test the crystal structure of the catalyst. The test method was as follows: the crystal phase of the catalyst was identified using a Japanese Rigaku D / max-RA X-ray diffractometer. The diffractometer detector was a scintillation counter, with characteristic X-rays of the element as the excitation source, Cu Ka rays, monochromatic wavelength λ=1.54056 Å, tube voltage 40 kV, tube current 100 mA, scanning range 5~80 °, and continuous scanning rate 5 ° / min.
[0054] The reduction performance of the catalyst was tested by H2-programmed temperature reduction (H2-TPR). Test method: The sample was tested by H2-TPR using FineSorb-3010D fully automatic chemisorption instrument from Pantech. The temperature program range was 25-500 °C, the reducing gas was 10% H2+90% Ar mixed gas, the flow rate was 30 mL / min, the heating rate was 10 °C / min, and the TPR curve was obtained by TCD detection of the change in H2 mass fraction during the heating process.
[0055] The basic strength and number of basic sites of the catalyst were tested by CO2-TPD. Test method: The samples were tested by CO2-TPD using FineSorb-3010D fully automatic chemisorption instrument from Pantech. 100 mg of the catalyst sample was weighed, heated to 250 °C for pretreatment, cooled to 100 °C, and then adsorbed with CO2 (30 ml / min) for 30 min. Then, He (flow rate of 30 ml / min) was purged at 100 °C until the chromatographic baseline was stable. The CO2 was desorbed by temperature programming (100-600 °C), with a flow rate of 30 mL / min and a heating rate of 10 °C / min. The signal of the desorbed CO2 was detected by a thermal conductivity cell detector.
[0056] The instrument model for the in-suit DRIFT test was Nicoletis50 FT-IR, the in-situ cell window was CaF2, the catalyst loading was 100 mg, and the sample was placed in the in-situ cell for reduction pretreatment at 300 °C in a 10% H2 / N2 (30 mL / min) atmosphere for 2 h. After the pretreatment, N2 (30 mL / min) was purged for 30 min and the reaction gas was switched to 10% CO2-40% H2-Ar (30 mL / min). The number of scans was 128 and the resolution was 4 cm -1 , the test temperature is 450 °C.
[0057] High temperature qualitative test method for silicon-aluminum composite oxide carrier: a predetermined amount of silicon-aluminum composite oxide particles are loaded into a stainless steel tube fixed bed reactor, water is introduced by bubbling at room temperature, and the fixed bed temperature is maintained at 550 o C, water vapor was continuously introduced for 6 hours, and then the temperature was lowered to room temperature. The silicon-aluminum composite oxide particles were taken out and strength tested. Comparative analysis of 550 o C Changes in particle strength after water vapor treatment.
[0058] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.
[0059] Embodiment 1:
[0060] Weigh 4.210g of quick-release powder (alumina content is 95%), add 9.824g of deionized water, stir until dissolved, weigh 61.538g of sodium silicate solution (wherein the SiO2 content is 26wt%), add to the quick-release powder solution, stir until mixed evenly, add 299.765g of 10% sulfuric acid solution dropwise, stir in a 50℃ water bath, gradually form a white sol, continue stirring until the sol viscosity reaches 1500mPa·S, centrifuge and wash the sol until the conductivity of the filtrate is less than 200μs / cm, and precipitate at 120℃. ℃ and dried to obtain a white powder, to which 30 g of starch was added for rolling and balling to obtain a spherical silicon-aluminum composite oxide carrier, marked as SiO2-Al2O3 (80-20), which means that the ratio of Si to Al meets the requirement that the total mass of SiO2 and Al2O3 is 100%, and the mass ratio of SiO2 to Al2O3 is 80:20, the same below.
[0061] Weigh 6.074g Cu(NO3)2·3H2O, 4.117g 50wt% Mn(NO3)2 solution, and 1.261g Ce(NO3)3·6H2O, dissolve them in water and stir them evenly to obtain a mixed solution, which is then impregnated on the above-mentioned water-resistant silicon-aluminum composite oxide support (mass of about 20g) and ultrasonically impregnated for 1h. After drying, the mixture is heated at 100°C. o C for 10 h and calcined at 450 ℃ for 4 h to obtain a 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3 catalyst, which means that in the catalyst, based on SiO2-Al2O3 as the measurement basis, CuO accounts for 10% of the mass of SiO2-Al2O3, MnO2 accounts for 5%, and CeO2 accounts for 2.5%, the same below.
[0062] Example 2
[0063] A 10% CuO-5% Fe2O3-2.5% CeO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that 4.117 g of 50% Mn(NO3)2 solution was replaced with 5.060 g of Fe(NO3)3·9H2O.
[0064] Example 3
[0065] A 10%CuO-2.5%MnO2-2.5%Fe2O3-2.5%CeO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that the 50% Mn(NO3)2 solution was replaced with 2.058 g of 50% Mn(NO3)2 solution and 2.530 g of Fe(NO3)3·9H2O.
[0066] Example 4
[0067] A 10%CuO-5%MnO2-2.5%ZnO / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that 1.261g Ce(NO3)3·6H2O was replaced by 1.827g Zn(NO3)2·6H2O.
[0068] Example 5
[0069] A 10%CuO-5%Fe2O3-2.5%ZnO / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that 4.117g of 50% Mn(NO3)2 solution was replaced by 5.060g Fe(NO3)3·9H2O, and 1.261g Ce(NO3)3·6H2O was replaced by 1.827g Zn(NO3)2·6H2O.
[0070] Example 6
[0071] A 10%CuO-2.5%MnO2-2.5%Fe2O3-2.5%ZnO / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that 4.117g of 50% Mn(NO3)2 solution was replaced by 2.058g of 50% Mn(NO3)2 solution and 2.530g of Fe(NO3)3·9H2O, and 1.261g of Ce(NO3)3·6H2O was replaced by 1.827g of Zn(NO3)2·6H2O.
[0072] Example 7
[0073] A 10%CuO-5%MnO2-2.5%ZrO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that 1.261g Ce(NO3)3·6H2O was replaced by 1.742g Zr(NO3)4·5H2O.
[0074] Example 8
[0075] A 10%CuO-5%Fe2O3-2.5%ZrO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1. The difference was that 4.117 g of 50% Mn(NO3)2 solution was replaced by 5.060 g of Fe(NO3)3·9H2O, and 1.261 g of Ce(NO3)3·6H2O was replaced by 1.742 g of Zr(NO3)4·5H2O.
[0076] Example 9
[0077] A 10%CuO-2.5%MnO2-2.5%Fe2O3-2.5%ZrO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that 4.117g of 50% Mn(NO3)2 solution was replaced by 2.058g of 50% Mn(NO3)2 solution and 2.530gFe(NO3)3·9H2O, and 1.261g Ce(NO3)3·6H2O was replaced by 1.742g Zr(NO3)4·5H2O.
[0078] Example 10
[0079] A 1%CuO-7.5%MnO2-7.5%CeO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that the amount of Cu(NO3)2·3H2O was 0.607 g, the amount of 50%Mn(NO3)2 solution was 6.175 g, and the amount of Ce(NO3)3·6H2O was 3.783 g.
[0080] Embodiment 11
[0081] A 15%CuO-0.5%MnO2-0.5%CeO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that the amount of Cu(NO3)2·3H2O was 9.112 g, the amount of 50%Mn(NO3)2 solution was 0.412 g, and the amount of Ce(NO3)3·6H2O was 0.252 g.
[0082] Example 12
[0083] The SiO2-Al2O3 (96-4) carrier was prepared according to the method of Example 1, except that the amount of quick de-powdering was 0.842 g, the amount of sodium silicate solution was 73.846 g, and the amount of 10% H2SO4 was 321.286 g.
[0084] Embodiment 13
[0085] The SiO2-Al2O3 (90-10) carrier was prepared according to the method of Example 1, except that the amount of quick de-powdering was 2.105 g, the amount of sodium silicate solution was 69.231 g, and the amount of 10% H2SO4 was 313.216 g.
[0086] Embodiment 14
[0087] The SiO2-Al2O3 (70-30) carrier was prepared according to the method of Example 1, except that the amount of quick de-powdering was 6.316 g, the amount of sodium silicate solution was 53.846 g, and the amount of 10% H2SO4 was 286.314 g.
[0088] Embodiment 15
[0089] The SiO2-Al2O3 (60-40) carrier was prepared according to the method of Example 1, except that the amount of quick de-powdering was 8.421 g, the amount of sodium silicate solution was 46.154 g, and the amount of 10% H2SO4 was 272.863 g.
[0090] Example 16
[0091] The SiO2-Al2O3 (50-50) carrier was prepared according to the method of Example 1, except that the amount of quick de-powdering was 10.526 g, the amount of sodium silicate solution was 38.461 g, and the amount of 10% H2SO4 was 259.412 g.
[0092] Embodiment 17
[0093] The SiO2-Al2O3 (80-20) carrier was prepared according to the method of Example 1, except that the amount of 10% H2SO4 used was 599.529 g.
[0094] Embodiment 18
[0095] The SiO2-Al2O3 (80-20) carrier was prepared according to the method of Example 1, except that the amount of 10% H2SO4 used was 149.882 g.
[0096] Comparative Example 1
[0097] 76.923 g of sodium silicate solution (SiO2 content is 26%) was weighed, and 326.667 g of sulfuric acid solution with a mass concentration of 10% was added dropwise. The mixture was stirred in a 50 °C water bath to gradually form a transparent sol. The stirring was continued until the sol viscosity reached 1500 mPa·S. The sol was centrifuged and washed until the conductivity of the filtrate was lower than 200 μs / cm. The sol was dried at 120 °C to obtain a transparent powder. 0.6 g of starch was added for ball rolling to obtain a spherical silica carrier, which was marked as SiO2.
[0098] Weigh 6.074g Cu(NO3)2·3H2O, 4.117g 50wt% Mn(NO3)2 solution, and 1.261g Ce(NO3)3·6H2O, dissolve them in water and stir them evenly to obtain a mixed solution, which is then impregnated on the above-mentioned SiO2 carrier (mass of about 20g) and ultrasonically impregnated for 1 h. After drying, the mixture is heated at 100°C. o C for 10 h and calcined at 450 ℃ for 4 h to obtain 10%CuO-5%MnO2-2.5%CeO2 / SiO2 catalyst.
[0099] Comparative Example 2
[0100] Weigh 21.053 g of quick-release powder (alumina content is 95%), add 49.124 g of deionized water, stir until dissolved, add 192.157 g of sulfuric acid solution with a mass concentration of 10% dropwise, stir in a 50 °C water bath, gradually form a white sol, continue stirring until the sol viscosity reaches 1500 mPa·S, centrifuge and wash the sol until the conductivity of the filtrate is less than 200 μs / cm, dry at 120 °C to obtain a white powder, add 0.6 g of starch for rolling ball forming, and obtain a spherical alumina carrier, marked as Al2O3.
[0101] Weigh 6.074g Cu(NO3)2·3H2O, 4.117g 50wt% Mn(NO3)2 solution, and 1.261g Ce(NO3)3·6H2O, dissolve them in water and stir them evenly to obtain a mixed solution, which is then impregnated on the above Al2O3 support (mass of about 20g) and ultrasonically impregnated for 1 h. After drying, the mixture is heated at 100°C. o C for 10 h and calcined at 450 ℃ for 4 h to obtain 10%CuO-5%MnO2-2.5%CeO2 / Al2O3 catalyst.
[0102] Comparative Example 3
[0103] A 10% CuO / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that the amount of 50% Mn(NO3)2 solution and Ce(NO3)3·6H2O used was 0.
[0104] Comparative Example 4
[0105] A 10%CuO-5%MnO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1, except that the amount of Ce(NO3)3·6H2O used was 0.
[0106] Comparative Example 5
[0107] A 10% CuO-5% Fe2O3 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1. The difference was that 4.117 g of 50% Mn(NO3)2 solution was replaced by 5.060 g of Fe(NO3)3·9H2O, and the amount of Ce(NO3)3·6H2O was 0.
[0108] Comparative Example 6
[0109] A 10% CuO-2.5% CeO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1. The difference was that the amount of 50% Mn(NO3)2 solution was 0 and the amount of Ce(NO3)3·6H2O was 1.261 g.
[0110] Comparative Example 7
[0111] A 10% CuO-2.5% ZnO / SiO2-Al2O3 catalyst was prepared according to the method of Example 1. The difference was that the amount of 50% Mn(NO3)2 solution was 0, and 1.261 g Ce(NO3)3·6H2O was replaced by 1.827 g Zn(NO3)2·6H2O.
[0112] Comparative Example 8
[0113] A 10% CuO-2.5% ZrO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1. The difference was that the amount of 50% Mn(NO3)2 solution was 0, and 1.261 g Ce(NO3)3·6H2O was replaced by 1.742 g Zr(NO3)4·5H2O.
[0114] Comparative Example 9
[0115] The SiO2-Al2O3 (40-60) carrier was prepared according to the method of Example 1, except that the amount of quick de-powdering was 12.632 g, the amount of sodium silicate solution was 30.769 g, and the amount of 10% H2SO4 was 245.961 g.
[0116] Comparative Example 10
[0117] A 15% CuO-2.5% CeO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1. The difference was that the amount of Cu(NO3)2·3H2O used was 9.112 g, and the amount of 50% Mn(NO3)2 solution used was 0.
[0118] Comparative Example 11
[0119] The 11.5%CuO-6%MnO2 / SiO2-Al2O3 catalyst was prepared according to the method of Example 1. The difference was that the amount of Cu(NO3)2·3H2O was 6.986 g, the amount of 50% Mn(NO3)2 solution was 4.940 g, and the amount of Ce(NO3)3·6H2O was 0.
[0120] The characterization data of the carriers in various embodiments and comparative examples are shown in Table 1.
[0121] Among them, the specific surface area and pore volume are obtained by BET test; the strength is obtained by strength tester test.
[0122] Table 1 Characterization data of carriers
[0123]
[0124] It can be seen from Table 1 that although the SiO2 carrier in Comparative Example 1 has a higher specific surface area and pore volume, the particle breakage rate when encountering liquid water is as high as 83%, and after 550 o After the water vapor treatment, the particle strength decreased significantly (by 59.3%), which is easy to cause powdering in industrial applications, increase pressure drop, and affect normal use; the specific surface area and pore volume of the Al2O3 carrier in Comparative Example 2 are both low, and the particle breakage rate when encountering liquid water is 1.5%. o After the water vapor treatment, the particle strength decreased by 24.5%. Compared with Comparative Example 2, the specific surface area and pore volume of the silicon-aluminum composite oxide carrier prepared in the embodiment were significantly larger than those of the Al2O3 carrier, and the breakage rate when exposed to liquid water was less than 1%. o After the C water vapor treatment, the particle strength decreased by less than 10%, and the performance was significantly better than that of the Al2O3 carrier. It can be seen from Examples 1, 12-16 and Comparative Example 9 that with the increase of silicon content, the specific surface area and pore volume of the silicon-aluminum composite oxide carrier increased. In Examples 1 and 17-18, the amount of sulfuric acid was changed, among which the amount of sulfuric acid in Example 18 was the lowest, the amount in Example 17 was the highest, and Example 1 was in the middle. It can be seen from Examples 1, 17 and 18 that the increase in the amount of sulfuric acid helps to increase the specific surface area and pore volume of the silicon-aluminum composite oxide carrier, but it has an impact on the breakage rate and 550% when encountering liquid water. o C The water vapor treatment has little effect on the change of particle strength.
[0125] Figure 1 The CO2-TPD spectra of the carriers in the embodiments and comparative examples are shown in FIG. Figure 1 It can be seen that compared with the Al2O3 carrier, the alkalinity on the SiO2 carrier is relatively weak, but the number of weak alkaline sites is significantly higher than that of Al2O3. Compared with the SiO2 carrier, as the silicon oxide content decreases, the alkalinity of the weak alkaline sites on the silicon-aluminum composite oxide carrier gradually increases, but the number of weak alkaline sites gradually decreases. At the same time, the alkalinity of the medium-strong alkaline sites gradually weakens, thereby forming alkaline sites with moderate alkalinity and a large number. In the CO2 catalytic conversion reaction process, CO2 adsorption is the first step. Alkaline sites with moderate alkalinity and a large number help promote the formation of moderate adsorption between CO2 and the silicon-aluminum composite oxide carrier, thereby promoting CO2 adsorption and catalytic conversion, and helping to improve the CO2 conversion rate.
[0126] The characterization and performance evaluation data of the catalysts in each embodiment and comparative example are shown in Table 2.
[0127] Among them, the specific surface area, pore volume and pore size are obtained by BET test; the CuO grains are obtained by XRD test, and the CO2 conversion rate and CO selectivity are obtained by the performance evaluation test of the catalyst.
[0128] Table 2 Characterization and evaluation data of catalysts
[0129]
[0130] It can be seen from Table 2 that compared with the SiO2-Al2O3 (80-20) carrier, after the metal is loaded, the specific surface area and pore volume of the catalyst in Examples 1-11 are reduced to a certain extent. This is because the metal covers a portion of the surface of the silicon-aluminum composite oxide carrier and blocks part of the pores.
[0131] Figure 2 The XRD spectra of the catalyst and the carrier in Example 1 and Comparative Examples 3, 4 and 6 are shown in FIG. Figure 2 It can be found that 2θ=23.5 o The diffraction peak at 2θ is attributed to amorphous aluminum silicate (SiO2-Al2O3 carrier). When 10% CuO is loaded on the carrier, 2θ=35.5 o , 38.8 o There is an obvious CuO characteristic diffraction peak at 2θ=28.6 o , 47.8 o The characteristic diffraction peak of CeO2 appears obviously at 10%. By comparing the XRD spectra of 10%CuO / SiO2-Al2O3 and 10%CuO-5%MnO2 / SiO2-Al2O3, it can be found that the introduction of the second active component MnO2 significantly reduces the characteristic diffraction peak of CuO, which indicates that the second active component MnO2 effectively promotes the high dispersion of the first active component CuO on the carrier surface and helps to reduce the CuO grain size (as shown in Table 2). By comparing the XRD spectra of 10%CuO-5%MnO2 / SiO2-Al2O3, 10%CuO-2.5%CeO2 / SiO2-Al2O3, and 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3, it can be found that after the addition of CeO2 additive, the characteristic diffraction peaks of CuO and CeO2 are not observed in the XRD spectrum of 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3, which indicates that under the promotion of CeO2 additive, CuO and CeO2 form a uniform solid solution structure, further improving the dispersion of CuO and reducing the CuO grain size (as shown in Table 2), which helps to stabilize the first active component CuO, thereby improving the stability of the catalyst.
[0132] Figure 3The H2-TPR spectra of the catalysts in Example 1 and Comparative Examples 3, 4 and 6 are shown in Table 1. By comparing the H2-TPR spectra of 10%CuO / SiO2-Al2O3 and 10%CuO-2.5%CeO2 / SiO2-Al2O3, it can be found that the addition of CeO2 additive significantly reduces the reduction temperature and improves the reduction performance of CuO. o A shoulder peak appears around C, which indicates that after the addition of CeO2 additive, the amount of highly dispersed CuO on the surface is greatly increased, thereby reducing the reduction temperature of CuO. Comparing the H2-TPR spectra of 10%CuO / SiO2-Al2O3 and 10%CuO-5%MnO2 / SiO2-Al2O3, it can be found that since the reduction temperature of MnO2 is higher than that of CuO, when the second active component MnO2 is added, a synergistic effect is formed between CuO and MnO2, resulting in a slight shift of the reduction temperature of the 10%CuO-5%MnO2 / SiO2-Al2O3 catalyst toward high temperature. Combined with the XRD results, it can be concluded that the electronic effect between Cu and Mn causes changes in the valence distribution of Cu on the catalyst surface, causing Cu to be highly dispersed on the catalyst surface. Comparison of the H2-TPR spectra of 10%CuO-5%MnO2 / SiO2-Al2O3 and 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3 further verified that the addition of CeO2 additive can significantly reduce the reduction temperature, promote the reduction of CuO, and improve the reduction performance of the catalyst. In summary, the addition of the second active component MnO2 forms a synergistic effect between CuO and MnO2, and the electronic effect between Cu and Mn optimizes the valence distribution of Cu on the catalyst surface and improves the dispersion. The addition of additive CeO2 helps to improve the reduction performance of the catalyst, increase the number of highly dispersed CuO species on the surface, and reduce the reduction temperature.
[0133] CO2 catalytic conversion performance test
[0134] The catalytic conversion performance of CO2 of the catalysts in the examples and comparative examples was evaluated by using a stainless steel tube fixed bed reactor. The process conditions used for the evaluation were: the catalyst loading was 1 mL, the feed gas composition was 10% CO2-30% H2-60% Ar, the reaction temperature was 300 o C, gas phase space velocity is 12000h -1 The product was analyzed online by gas chromatography GC2060, and the activity evaluation results are shown in Table 2.
[0135] According to the data of CO2 conversion rate and CO selectivity in Table 2, by comparing Example 1 and Comparative Examples 1-2, it can be found that compared with 10%CuO-5%MnO2-2.5%CeO2 / SiO2 and 10%CuO-5%MnO2-2.5%CeO2 / Al2O3, the 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3 catalyst has higher CO2 conversion rate and CO selectivity. Combined with the CO2-TPD data of the carrier, it can be seen that the alkalinity of the SiO2 carrier is weak, the alkalinity of Al2O3 is strong, and the SiO2-Al2O3 composite carrier has alkaline sites with moderate alkaline strength and more alkaline sites. Therefore, the SiO2-Al2O3 composite carrier is more conducive to CO2 adsorption and conversion, promotes the efficient conversion of intermediate products into the target product CO, and thus improves the CO2 conversion rate and CO selectivity. By comparing Comparative Examples 3-8, it can be found that compared with the 10%CuO / SiO2-Al2O3 catalyst, the addition of the second active component and the additive improves the CO2 conversion rate and CO selectivity to varying degrees, among which the second active component MnO2 and the additive CeO2 have a better promoting effect. By comparing Examples 1-9 and Comparative Examples 4-6, it can be found that when the second active component and the additive are present at the same time, the CO2 conversion rate and CO selectivity on the catalyst will be higher, especially the 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3 catalyst, at 300 o C, the CO2 conversion rate reached 23.08%, close to the thermodynamic equilibrium value, and the CO selectivity was 100%.
[0136] Figure 4 The in-situ infrared spectra of the catalysts in Example 1 and Comparative Examples 3, 4 and 6 are shown in FIG. Figure 4 From the data of CO selectivity in Table 2, it can be found that on the 10%CuO / SiO2-Al2O3 catalyst, in addition to the product CO, there are also intermediate products such as formic acid, carboxylates, carbonates, and methane by-products, while the 10%CuO-5%MnO2 / SiO2-Al2O3 and 10%CuO-2.5%CeO2 / SiO2-Al2O3 catalysts only have weak methane by-products, and no by-products and intermediates are observed on the 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3 catalyst, only the target product CO. This shows that the addition of the second active component MnO2 and CeO2 additives effectively promotes the timely conversion of intermediate products into the target product CO, and inhibits the CO2 methanation side reaction at low temperature, significantly improving the CO2 conversion rate and CO selectivity.
[0137] CO2 catalytic conversion performance test under different reaction process conditions
[0138] The CO2 catalytic conversion performance of the catalyst in Example 1 was evaluated using a stainless steel tube fixed bed reactor. The process conditions used for the evaluation were: catalyst loading of 1 mL, CO2 concentration of 10%, reaction pressure of 0.1-2.0 MPa, reaction temperature of 300-550 °C. o C, gas phase space velocity is 3000~24000h -1 , H2 / CO2 is 1 to 4. The product was analyzed online by gas chromatography GC2060, and the activity evaluation results are shown in Table 3.
[0139] Table 3 Catalyst performance evaluation data in Example 1
[0140]
[0141] It can be seen from Table 3 that the CO2 conversion rate of the 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3 catalyst in Example 1 shows an increasing trend with increasing reaction temperature. This is because the CO2 reverse water gas shift reaction process is endothermic, and increasing the temperature helps to improve the CO2 conversion rate; increasing the reaction pressure slightly improves the CO2 conversion rate, but a small amount of methane by-product is produced; the reaction space velocity has little effect on the CO2 conversion rate and CO selectivity; with the increase of H2 / CO2, the CO2 conversion rate increases slightly, and the CO selectivity remains at 100%.
[0142] Catalyst stability performance test
[0143] The stability performance of the catalyst in Example 1 was evaluated using a stainless steel tube fixed bed reactor. The process conditions used for the evaluation were: the catalyst loading was 1 mL, the feed gas was 10% CO2-30% H2-60% Ar, the reaction pressure was atmospheric pressure, and the reaction temperature was 550 o C, gas phase space velocity is 12000h -1 The product was analyzed online by gas chromatography GC2060, and the activity evaluation results were as follows: Figure 5 shown.
[0144] Depend on Figure 5It can be seen that within 500 hours of continuous reaction, the CO2 conversion rate on the 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3 catalyst is maintained at about 54%, and the CO selectivity is always close to 100%, with good stability and no deactivation. Combined with the in-situ infrared results, it can be concluded that on the 10%CuO-5%MnO2-2.5%CeO2 / SiO2-Al2O3 catalyst, CO2 can be efficiently adsorbed and catalytically converted in time, and the intermediate products in the reaction process can be quickly converted into the target product CO, which does not occupy the active sites of the catalyst and does not block the pores of the catalyst. At the same time, there is no methanogenic side reaction, which makes the catalyst active sites remain stable for a long period of time, greatly improving the stability of the catalyst.
[0145] In summary, the CO2 catalytic conversion catalyst of the present invention, wherein the water-resistant silica-aluminum composite oxide carrier has a large specific surface area and a large pore volume, is conducive to the high dispersion of the active components, reduces the grain size of the active components, inhibits the aggregation and growth of the active components, and thus improves the stability of the catalyst; at the same time, the water-resistant silica-aluminum composite oxide carrier can withstand liquid water, and prevent a small amount of liquid water in industrial applications from causing the catalyst to pulverize, causing an increase in pressure drop, and thus improving the stability of the operation of the industrial device; in addition, the water-resistant silica-aluminum composite oxide carrier has good high thermal stability and water resistance, which improves the stability of the catalyst under high temperature and high humidity conditions and extends its service life. On the basis of the first active component CuO, the second active component is introduced to form a synergistic effect between the two active components. The electronic effect between the two changes the valence distribution of Cu, promotes the improvement of CuO dispersion, reduces the CuO grain size, and improves the catalytic activity; after the introduction of the auxiliary agent, the auxiliary agent forms a solid solution structure with CuO, further improves the dispersion of CuO, reduces the CuO grain size, and plays a role in stabilizing CuO and improving the stability of the catalyst. In addition, the addition of the auxiliary agent effectively reduces the reduction temperature of the catalyst, increases the amount of highly dispersed CuO on the surface, and thus improves the low-temperature activity of the catalyst. The addition of the second active component and the auxiliary agent promotes the efficient conversion of the intermediate product (formic acid, carboxylate, carbonate, etc.) into the target product CO, and also effectively inhibits the CO2 methanogenic side reaction, thereby greatly improving the high-temperature stability of the catalyst. The CO2 catalytic conversion catalyst of the present invention has a simple preparation process and low production cost, is conducive to industrial production and application, has significant economic advantages, and has broad prospects for industrial application.
[0146] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a CO2 catalytic conversion catalyst, characterized in that: The following steps are involved: (1) Weigh a silicon source and an aluminum source to prepare a silicon-aluminum aqueous solution, mix it with an inorganic acid aqueous solution, and stir to form a white sol until the viscosity reaches 1200-2000 mPa·S; (2) centrifuging, washing and drying the sol obtained in step (1) to obtain white silicon-aluminum composite oxide powder, adding a binder and rolling into balls to obtain a silicon-aluminum composite oxide carrier precursor; (3) Weighing a first active component precursor, a second active component precursor and an auxiliary component precursor, dissolving and stirring them with water as a solvent to obtain a mixed solution; (4) impregnating the silicon-aluminum composite oxide support precursor in step (3) in the mixed solution, drying, and calcining to obtain a CO2 catalytic conversion catalyst; In step (1), the H + , the molar ratio of the total amount of SiO2+Al2O3 in the silicon source and the aluminum source is 0.5~2:1; The CO2 catalytic conversion catalyst includes a silicon-aluminum composite oxide support, and a first active component, a second active component and an auxiliary component loaded on the silicon-aluminum composite oxide support, wherein the first active component is CuO, the second active component is an oxide of Mn and / or Fe, and the auxiliary component is an oxide of at least one of Ce, Zr or Zn, wherein the mass content of SiO2 in the silicon-aluminum composite oxide support is 50% to 80%, and the mass content of Al2O3 is 20% to 50%; the first active component is 1 to 15% of the mass of the silicon-aluminum composite oxide support, the second active component is 0.5 to 7.5% of the mass of the silicon-aluminum composite oxide support, and the auxiliary component is 0.5 to 7.5% of the mass of the silicon-aluminum composite oxide support.
2. The method for preparing a CO2 catalytic conversion catalyst according to claim 1, characterized in that: In step (1), the silicon source is selected from one or more of silica sol, sodium silicate, and silicon oxide powder; The aluminum source is selected from one or more of aluminum sol, pseudo-boehmite, quick-de-powder, and alumina powder; The inorganic acid is one or more of nitric acid, hydrochloric acid or sulfuric acid.
3. The method for preparing a CO2 catalytic conversion catalyst according to claim 1, characterized in that: In step (2), washing is performed once or repeatedly for multiple times until the conductivity of the filtrate is less than 200 μs / cm; The drying temperature is 100~120℃; The mass ratio of white silicon-aluminum composite oxide powder to binder is 1:(0.005-0.05), and the binder is one or more of silica sol, aluminum sol, bentonite, sodium methyl cellulose, starch, attapulgite, and kaolin.
4. The method for preparing a CO2 catalytic conversion catalyst according to claim 1, characterized in that: In step (3), the first active component precursor is copper nitrate; The second active component precursor is a nitrate of Mn and / or Fe; The auxiliary agent component precursor is nitrate of Ce and / or Zr.
5. The method for preparing a CO2 catalytic conversion catalyst according to claim 1, characterized in that: In step (4), the immersion process is specifically as follows: ultrasonic immersion for 0.5 to 2 h; The specific drying process is as follows: drying at 100-120 °C for 6-12 h; The specific calcination process is: calcination at 350~600 ℃ for 2~6 h.
6. A CO2 catalytic conversion catalyst, characterized in that: It is prepared based on the preparation method according to any one of claims 1 to 5, and the specific surface area of the catalyst is 350 to 650 m 2 / g, pore volume is 0.3~0.7 cm 3 / g, CuO grain size is less than 2nm.
7. Application of a CO2 catalytic conversion catalyst in CO2 reverse water gas shift reaction, characterized in that: The CO2 catalytic conversion catalyst as claimed in claim 6 is used.
Citation Information
Patent Citations
Cu-Zn-based catalyst used in reverse water gas shift reaction, and preparation method and application thereof
CN103230799A
Ir-based catalyst for reverse water-gas shift reaction as well as preparation and application thereof
CN106881082A
Copper-based catalyst for reverse water-gas shift reaction and preparation method therefor
CN107497439A
A catalyst for reverse water-gas shift reaction, its preparation and application
CN108144637B
Ni@Au core-shell nanocatalysts: their synthesis and application
CN110756197B